Region 4 of Rhizobium etli Primary Sigma Factor (SigA) Confers Transcriptional Laxity in Escherichia coli - Santillán, Orlando; Ramírez-Romero, Miguel A.; Lozano, Luis; Checa, Alberto; Encarnación, Sergio M.; Dávila, Guillermo (Frontiers in Microbiology, 2016)
Sigma factors are RNA polymerase subunits engaged in promoter recognition and DNA strand separation during transcription initiation in bacteria. Primary-sigma factors are responsible for the expression of housekeeping genes and are essential for survival. RpoD, the primary-sigma factor of Escherichia coli, a γ-proteobacteria, recognizes consensus promoter sequences highly similar to those of some α-proteobacteria species. Despite this resemblance, RpoD is unable to sustain transcription from most of the α-proteobacterial promoters tested so far. In contrast, we have found that SigA, the primary-sigma factor of Rhizobium etli, an α-proteobacteria, is able to transcribe E. coli promoters, although it exhibits only 48% identity (98% coverage) to RpoD. We have called this the transcriptional laxity phenomenon. Here, we show that SigA partially complements the thermo-sensitive deficiency of RpoD285 from E. coli strain UQ285 and that the SigA region σ4 is responsible for this phenotype. Sixteen out of 74 residues (21.6%) within region σ4 are variable between RpoD and SigA. Mutating these residues significantly improves SigA ability to complement E. coli UQ285. Only six of these residues fall into positions already known to interact with promoter DNA and to comprise a helix-turn-helix motif. The remaining variable positions are located on previously unexplored sites inside region σ4, specifically into the first two α-helices of the region. Neither of the variable positions confined to these helices seem to interact directly with promoter sequence; instead, we adduce that these residues participate allosterically by contributing to correct region folding and/or positioning of the HTH motif. We propose that transcriptional laxity is a mechanism for ensuring transcription in spite of naturally occurring mutations from endogenous promoters and/or horizontally transferred DNA sequences, allowing survival and fast environmental adaptation of α-proteobacteria.